Tinjauan Yuridik Perkawinan Beda Agama Dalam Perspektif Hukum Perkawinan dan Hak Asasi Manusia - Novian Angga Saputra (Al Ahkam, 2022)
The law has the function of providing certainty to human actions, the existence of Law No.1 of 1974 concerning Marriage has not been able to provide clear legal certainty such as interfaith marriages in Indonesia. Marriage is carried out using the laws of their respective religions, and in human rights, freedom of religion and marriage is something that cannot be interfered with. Research shows that the marriage law does not provide certainty for couples who hold interfaith marriages, there is still a blurring of norms regarding interfaith marriages and conflicting norms regarding the validity of marriages with freedom of religion, furthermore Interfaith marriages are considered discriminatory, because belief is a basic right that has been protected by law and no one is allowed to interfere with it, then this phenomenon causes consequences for one of the parties to submit to the belief of their partner.